Ti30Zr10Hf10Ni35Cu15 high-entropy shape memory alloy with tunable transformation temperature and elastocaloric performance by heat treatment - Yen-Ting Chang; Ming-Hao Lee; Ming-Wen Chu; Yi-Ting Hsu; Chih-Hsuan Chen (Materials Today Advances, 2023)
This work investigates the influence of heat treatments on a pseudo-binary Ti30Zr10Hf10Ni35Cu15 high-entropy shape memory alloy. Heat treatments on the alloy resulted in the formation of second phases and thus were able to adjust its transformation temperatures. This phenomenon results from the formation of H-phase and (Zr,Hf)7Cu10 phase during low-temperature and high-temperature aging, respectively. The superelasticity of solution-treated, 500 °C-aged and 700 °C-aged samples was tested under compression, and all samples exhibited nearly 5 % recoverable strain and 15 °C elastocaloric cooling capacity. Further cyclic compression tests confirmed their stability, with up to 75 % of the initial cooling capacity retained after 5000 compression cycles. Due to its high yield strength, the Ti30Zr10Hf10Ni35Cu15 high-entropy shape memory alloy showed great superelasticity and elastocaloric performance at various testing temperatures. Furthermore, with heat treatments, the austenitic transformation finishing temperature (Af) of the alloy was tunable to between −10 °C (furnace-cooled) and 60 °C (700 °C-aged) with promising functional performance. These features expand the application range of TiZrHfNiCu high-entropy shape memory alloys as potential superelastic and elastocaloric materials.